Photons from relativistic nuclear collisions. (30th November 2021) - Vormann, Hannah; Reichert, Tom; Spieles, Christian; Steinheimer, Jan; Bleicher, Marcus
Abstract: Collisions of atomic nuclei at relativistic velocities allow us to recreate the conditions encountered in neutron stars or in the early Universe micro-seconds after the Big Bang. These reactions are performed in today's largest accelerator facilities, e.g. at CERN in Geneva, at the relativistic heavy ion collider at Brookhaven, NY or in the planned FAIR facility in Darmstadt Germany. During such a collision the matter is heated to hundreds of MeV (billions of degrees) and compressed to densities of 3–10 times the density inside ordinary atomic nuclei (i.e. 10 17 –10 18 kg m −3 ). Usually these collisions are studied via the measurement of a multitude of strongly interacting particles, called hadrons, that are emitted at the end of the collision. However, some photons are also created. These photons are of special interest as they allow us to look into the early stage of the collisions. This is because they only interact electro-magnetically with the hadrons of the created fireball, which is a much weaker interaction compared to the strong interaction. This paper elucidates the physics of the photons and what can be learned from them.